Verificación de la marca de eclosión en los otolitos sagitales de larvas de Sardinella aurita (Pisces: Clupeidae) - Balza, María Alejandra; Marín, Bauman (Revista de Biología Tropical, 2000)
The study of otolith in larvae is important to determine fish age and growth, essential parameters in the study and management of fisheries resources. In this study, the formation of the hatching mark in Sardinella aurita was verified on ichthyoplankton samples collected off southern Cubagua island, Venezuela, from May 1998 to January 1999. The embryos were kept alive using a culture system until they hatched and daily a group of 10 to 30 larvae were fixed in 95% ethanol. An image analysis system was used to measure morphometric characteristics of larvae and sagittal otoliths. Following are mean values in newly hatched larvae: otolith hatching mark distance from nucleus 4.78 m (I.C 0.36 m, p 0.05 n= 30) increase width 1.46 m (I.C 0.17 μm, p 0.05, n= 30) and diameter 14.28 m (I.C 1.11 m, p 0.05, n = 30). The mean standard length of larvae at age O was 3.31 mm (I.C 0.08 mm, p 0.05, n= 200). The identification of the hatching mark allows the exact calculation of the number of rings in larvae from the natural environment.